Indonesia’s Challenge to Combat Climate Change Using Clean Energy - Rudi Irawan; Afzeri Tamsir; Riza Muhida (International Journal of Engineering Science and Technology Development (IJEST), 2013)
Indonesia as the biggest archipelago country and situated in equator is very vulnerable to the adverse effect of climate change. There are two main categories of efforts to handle the issues in climate change; that are how to mitigate it and how to adapt to the change. One of the main culprits of climate change is the emission of carbon gas due to fossil fuel energy utilization contributing 302 million tonnes CO2equivalent.President of the Republic of Indonesia in 2009 in the G-20 Meeting, Pittsburgh, USA, and in 2010 in COP 15 UNFCCC, Copenhagen, Denmark issued the national voluntary target to reduce greenhouse gas emission by year 2020 as much as 26% from business-as-usual by national domestic efforts. This emission reduction will further be improved as much as 41% from business-as-usual by international supports. The Government of Indonesia issued a national action plan to reduce greenhouse gases emission which is enforced by Presidential Regulation No. 61/2011. To achieve this target in energy sector,REFF-Burn (Reducing Emission from Fossil Fuel Burning) concept has been proposed by Sumiarso. Based on REFF-Burn Technology Portfolio, reducing emission from fossil-fuel burning is categorized in three different stages, which are pre-combustion, during combustion and post-combustion. In pre-combustion stage, utilization of clean energy is one of the wise choices. The perspective of the clean energy resources and utilization in Indonesia is discussed in this paper.